Empowerment by Design? Women's Use of New Urbanist Neighborhoods in Suburbia. (September 2014) - Fagan, Charlotte; Trudeau, Dan
This paper investigates the potential of new urbanism (NU) to serve as a new neighborhood strategy for women. Survey and interview research examines the ways women in suburban NU neighborhoods of Minneapolis–St. Paul interact with the built environment to effect divisions of household labor and social isolation. The analysis shows that women use pedestrian-accessible mixed-use centers and neo-traditional design features (e.g., porches) to lessen the burden of domestic labor and foster social interaction. Despite these affordances, the paper argues that NU neighborhoods do not ultimately serve as resources in breaking patterns of social segregation or women's isolation in suburbia.